Digital Marketing Capabilities and MSME Competitiveness in the Industry 4.0 Era: An Integrative Literature Review - Mochammad Fahmi; Carnaval Rego Rio Sidabutar (International Journal of Business, Law, and Education, 2026)
This study examines how digital marketing contributes to the competitiveness of micro, small, and medium enterprises (MSMEs) in the Industry 4.0 era. Rather than treating social media, search engine optimization, content marketing, e-commerce, and online marketplaces as isolated promotional tools, the review conceptualizes them as a portfolio of complementary organizational capabilities. A structured integrative literature review was conducted to synthesize conceptual and empirical research on digital transformation, digital marketing adoption, customer engagement, and SME performance. The synthesis identifies five interrelated capability domains: social media interaction, content and search visibility, e-commerce and marketplace participation, customer data and analytics, and cross-channel integration. These capabilities influence performance through improved market visibility, customer engagement, trust, conversion, retention, and market learning. However, the relationship is contingent on digital literacy, managerial commitment, technological readiness, financial and human resources, logistics and payment infrastructure, and platform-related risks. The evidence supports a broadly positive association between digital marketing capability and MSME outcomes, but causal claims should remain cautious because much of the literature is cross-sectional, self-reported, and context-specific. The article contributes a capability-mechanism-outcome framework and a staged implementation agenda for MSME managers and policymakers. It concludes that sustainable competitiveness depends less on the adoption of a single platform than on the coordinated development, measurement, and continuous reconfiguration of digital marketing capabilities.